Board of directors’ characteristics and financial performance: a case study of selected hotels and restaurants in Sri Lanka - Priya, K.; Nimalathasan, B. (My University, 2013)
Abstract The boards of directors play a critical role in monitoring companies in Sri Lanka. However, it is possible that board director’s characteristics are important in the hotels and restaurants due to the nature of business and the effect of government regulations, both of which limit to managerial discretion. This study examines the relation between board of directors’ characteristics and financial performance among selected hotels and restaurants in Sri Lanka which covered selected hotels and restaurants in Sri Lanka over a period of past 5 years from 2008 to 2012. Correlation and regression analysis were used in the analysis. The result revealed that there is a significant relationship that exists between board of directors’ characteristics and financial performance among selected hotels and restaurants in Sri Lanka. The suggested Number of Women in Board (NWB) and Inside Directors (ISD) are significantly correlated with Return on Asset (ROA) at 5 percent level of significance. NWB and ISD are significantly correlated with Return on Equity (ROE) at 5 percent level of significance. At the same time CEO Duality (CEO DUAL) is significantly correlated with ROE at 1 percent level of significance. Finally the rest of other variables are not correlated. The results add insight on the relation between monitoring mechanisms and financial performance of hotels in an emerging market.
Keywords: job satisfaction employees